Identification of Pseudomonas Spp. That Increase Ornamental Crop Quality During Abiotic Stress - Nordstedt, Nathan P.; Chapin, Laura J.; Taylor, Christopher G.; Jones, Michelle L. (Frontiers in Plant Science, 2020)
The sustainability of ornamental crop production is of increasing growing concern to both producers and consumers. As resources become more limited, it is important for greenhouse growers to reduce production inputs such as water and chemical fertilizers, without sacrificing crop quality. Plant growth promoting rhizobacteria (PGPR) can stimulate plant growth under resource-limiting conditions by enhancing tolerance to abiotic stress and increasing nutrient availability, uptake, and assimilation. PGPR are beneficial bacteria that colonize the rhizosphere, the narrow zone of soil in the vicinity of the roots that is influenced by root exudates. In this study, in vitro experiments were utilized to screen a collection of 44 Pseudomonas strains for their ability to withstand osmotic stress. A high-throughput greenhouse experiment was then utilized to evaluate selected strains for their ability to stimulate plant growth under resource-limiting conditions when applied to ornamental crop production systems. The development of a high-throughput greenhouse trial identified two pseudomonads, P. poae 29G9 and P. fluorescens 90F12-2, that increased petunia flower number and plant biomass under drought and low-nutrient conditions. These two strains were validated in a production-scale experiment to evaluate the effects on growth promotion of three economically important crops: Petunia  hybrida, Impatiens walleriana, and Viola  wittrockiana. Plants treated with the two bacteria strains had greater shoot biomass than untreated control plants when grown under low nutrient conditions and after recovery from drought stress. Bacteria treatment resulted in increased flower numbers in drought-stressed P. hybrida and I. walleriana. In addition, bacteria treated plants grown under low-nutrient conditions had higher leaf nutrient content compared to the untreated plants. Collectively, these results show that the combination of in vitro and greenhouse experiments can efficiently identify beneficial Pseudomonas strains that increase the quality of ornamental crops grown under resource-limiting conditions.